2021
DOI: 10.1002/smll.202006541
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Al3+ Sites on Brønsted Acid Metal–Organic Frameworks for Glucose‐to‐Hydroxylmethylfurfural Transformation

Abstract: Abstract5‐hydroxylmethylfurfural (HMF) is a bio‐based chemical that can be prepared from natural abundant glucose by using combined Brønsted–Lewis acid catalysts. In this work, Al3+ catalytic site has been grafted on Brønsted metal–organic frameworks (MOFs) to enhance Brønsted–Lewis acidity of MOF catalysts for a one‐pot glucose‐to‐HMF transformation. The uniform porous structure of zirconium‐based MOFs allows the optimization of both acid strength and density of acid sites in MOF‐based catalysts by incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 59 publications
(14 reference statements)
1
26
0
Order By: Relevance
“…[12][13] In order to make full use of biomass resource, fine chemicals, and biological liquid fuel oil can be prepared by hydrogenation, oxidation, hydrolysis, esterification, reductive depolymerisationenzymatic hydrolysis, and catalytic pyrolysis. [14][15][16][17][18][19][20][21][22][23][24][25][26] 5-hydroxymethylfurfural (HMF) is a very momentous platform compound, [27][28][29][30] HMF was obtained though the dehydration of biomass-derived carbohydrates, such as glucose, [31][32][33][34][35] fructose, [36][37][38][39][40] sucrose, [41][42][43][44][45] inulin, [46][47][48][49][50] cellobiose [51][52][53][54][55] and cellulose. [29,[56][57][58]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13] In order to make full use of biomass resource, fine chemicals, and biological liquid fuel oil can be prepared by hydrogenation, oxidation, hydrolysis, esterification, reductive depolymerisationenzymatic hydrolysis, and catalytic pyrolysis. [14][15][16][17][18][19][20][21][22][23][24][25][26] 5-hydroxymethylfurfural (HMF) is a very momentous platform compound, [27][28][29][30] HMF was obtained though the dehydration of biomass-derived carbohydrates, such as glucose, [31][32][33][34][35] fructose, [36][37][38][39][40] sucrose, [41][42][43][44][45] inulin, [46][47][48][49][50] cellobiose [51][52][53][54][55] and cellulose. [29,[56][57][58]…”
Section: Introductionmentioning
confidence: 99%
“…In order to make full use of biomass resource, fine chemicals, and biological liquid fuel oil can be prepared by hydrogenation, oxidation, hydrolysis, esterification, reductive depolymerisationenzymatic hydrolysis, and catalytic pyrolysis [14–26] . 5‐hydroxymethylfurfural (HMF) is a very momentous platform compound, [27–30] HMF was obtained though the dehydration of biomass‐derived carbohydrates, such as glucose, [31–35] fructose, [36–40] sucrose, [41–45] inulin, [46–50] cellobiose [51–55] and cellulose [29,56–60] . Microwave technology is a simple and efficient conversion technology that can convert biomass to HMF.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, ADES- 4 with functionally decorated hydroxyl and acylamide groups may synergistically be involved in the two-step process involving glucose to fructose conversion followed by dehydration favoring efficient product yield of HMF. It is well documented in the literature that the mechanism involving glucose to HMF conversion proceeds via isomerization followed by dehydration. , In the first catalytic cycle, fructofuranose was generated via a 1,2-hydride transfer, followed by cyclization from α-glucopyranose. The probable mechanism in the present investigation also follows the same pathway in which synergistic effect engendered through the surface, the layered channels, and the availability of Brønsted acid sites on functionalized linkers in both MOFs plays an important role in the conversion of glucose/fructose to HMF.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Oozeerally and Kongpatpanich have investigated the catalytic performance of UiO-66-based materials with different modifications for one pot reaction of GLU to HMF in water independently. 108,109 It was found that the catalytic performance of these MOFs could be modulated via introducing structural defects, modulating the particle size, and introducing functional groups.…”
Section: From Glu To Hmfmentioning
confidence: 99%